Fenomena Gerakan Hijrah Virtual: Studi Grup WhatsApp Kelas Cewe Hijrah (September) - Nofia Natasari (Dakwah Institut PTIQ Jakarta, 2023)
In the era of globalization and advances in information technology, the virtual migration movement has become an interesting phenomenon that reflects changes in people's behavior in facing the challenges of the modern world. This research explores the Virtual Hijrah Movement in the Hijrah Girls Class (September), an online community that adopts a faith-based lifestyle, particularly Islam, in a digital context. Through a qualitative approach, this study explores the motivation and meaning of hijra and its impact on members' daily lives. The results of the interviews showed positive changes in the quality of worship, increased knowledge, and the formation of positive relationships. Within the theoretical framework of symbolic interactionism, this study looks at how group members create meaning through virtual social interaction. The conclusion of this study provides insight into the potential and challenges of the Virtual Hijra Movement in the context of the social and spiritual development of modern society.